Hospital mortality rates between 2015 and 2022: a comparison between the pre-pandemic and pandemic period shows that COVID-19 is a critical health problem - Wolf, Jonas Michel; Petek, Helena; Gasparetto Maccari, Juçara; Nasi, Luiz Antonio (Clinical and Biomedical Research, 2023)
Introduction: COVID-19 caused 6.2 million deaths in the world. The present study aims to evaluate hospital mortality rates from 2015 to 2022, to compare the pre and during the pandemic period. Methods: The study was carried out in a private hospital in southern Brazil. 174,013 hospital discharges between January 2015 and March 2022 were analyzed. Pearson’s chi-squared test was performed to evaluate the mortality rate by year. Differences between mortality rates before and during the pandemic was tested with Student’s t-test. P-values < 0.05 for all tests were considered significant. Results: Mortality rates were 2.29% in 2015; 2.37% in 2016; 2.25% in 2017; 2.31% in 2018; 2.46% in 2019; 3.45% in 2020; 3.58% in 2021 and 2.77% in 2022 (p < 0.01). The mortality for 2020 and 2021 was higher than in the other years (3.50% ± 0.14 vs 2.34% ± 0.05; p < 0.01). Conclusion: The mortality rates were significantly higher in the years 2020 and 2021, demonstrating that COVID-19 is a critical health problem.